Measurement of Lead content in Claris batrachus from Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati; Sedijani, Prapti (Jurnal Biologi Tropis, 2026)
Catfish (Clarias batrachus) is one of the fish species that is an indicator of pollution in Lake Taliwang. This study aims to determine the levels of Lead (Pb) in the muscles of Catfish (Clarias batrachus). Consumers who consume Catfish exposed to Pb need to be protected from their health. Catfish were caught in the waters of Lake Taliwang using gill nets. There are 2 data collection stations, namely on the east and west sides of the lake. Fish samples were taken as many as 2 fish for each station. Furthermore, each fish sample was wrapped in a plastic bag and stored in a sample box. The fish samples were then analyzed at the West Nusa Tenggara Health, Testing and Calibration Laboratory Center. The data analysis method was carried out by taking muscle tissue from the fish and then analyzing the Pb heavy metal content using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The conclusion of this study is that the Pb heavy metal content in Clarias batrachus is less than 0.5 ppm which indicates that the fish is still safe because the Pb level is still below the threshold according to applicable regulations in Indonesia.